Invisible Fragility in Industrial Medical Materials: A Theoretical Framework for Functional Performance Degradation without Structural Failure - Kareem, Rasha Abdul (American Journal of Biology and Natural Sciences, 2026)
This research investigates the concept of latent fragility in biomedical (medical-grade) materials, focusing on analyzing the phenomena that lead to progressive functional degradation without apparent structural failure. The research presents a comprehensive theoretical and conceptual framework of latent fragility, reviewing modern definitions and distinguishing it conventional fragility, It also discusses the physical, mechanical, and biological theoretical frameworks that explain the phenomenon of gradual loss of functional efficiency. This research analyzes structural and microstructural characteristics of biomedical polymers, metallic biomaterials, and biocomposites, demonstrating how these properties affect a material's resistance to repeated mechanical stresses, chemical and electrochemical corrosion, and microbiologically induced changes, It also addresses the concept of service lifetime, functional performance indicators, and the distinctions between functional degradation and structural deterioration, emphasizing the importance of early diagnosis of latent fragility using advanced techniques such as electron microscopy, spectroscopic analyses, and micromechanical testing methods. Furthermore, the research discusses engineering and biomedical strategies for improving material reliability, including material design optimization, manufacturing process optimization, and the implementation periodic maintenance protocols and clinical follow-up, It underscores the role of these strategies in extending service life and reducing clinical risks. The research concludes by emphasizing the need to integrate theoretical understanding with practical applications, develop accurate predictive simulation models for long-term material performance, and propose future research aimed at developing more reliable and efficient biomedical materials and devices. This research demonstrates that understanding latent fragility is not merely a scientific matter but a vital component in improving medical safety, device reliability, and the long-term sustainability of functional performance in biomedical materials.